Penentuan Jumlah Teller yang Optimal Dengan Metode Antrian di PT Bank Haga - Abbas, Bahtiar S.; Raymond, Raymond (Journal the Winners: Economics, Business, Management, and Information System Journal, 2003)
This article presents the optimization of the number of tellers at the service counter at PT BANK Haga. Its done by comparing the some alternatives related to the number of tellers employed. Conclusion indicates that optimal condition is that 5 tellers at Abdul Muis Branch and 4 tellers at Daan Mogot Branch.